ANALISIS KESALAHAN PESERTA DIDIK DALAM MENYELESAIKAN SOAL PEMECAHAN MASALAH MATEMATIKA DITINJAU DARI LANGKAH POLYA DI KELAS XI MIPA SMA NEGERI 1 ENAM LINGKUNG - Tessy Muharnida (Jurnal Edukasi dan Penelitian Matematika, 2021)
Mathematical problem solving is one of the competencies that must be mastered by students. However, in class XI MIPA SMA Negeri 1 Enam Lingkung is still relatively low so that many students make mistakes in working on problem solving problems. Errors made by students need to be identified in order to improve the quality of learning activities by conducting research to analyze the errors of class XI MIPA students at SMA Negeri 1 Enam Lingkung with the aim of knowing the most dominant types of errors made by students in solving math problem solving problems in the material. Linear program and find out the factors that cause the error.The type of research used is descriptive qualitative research. The research subjects were students of class XI MIPA 5 SMA Negeri 1 Enam Lingkung for the academic year 2021/2022 which was held in August-September 2021. The data were obtained from observations, written tests on Linear Program materials and interviews.In the results of the research conducted, it shows that the most dominant type of error made by students is the error in planning problem solving with a percentage of 36.42%. While the other types of errors are errors in understanding the problem by 7.85%, errors in implementing the problem-solving plan by 18.57%, and errors in re-checking the solutions obtained as much as 23.57%. The causes of the mistakes made by these students are not accustomed to discussing or working on mathematical problem solving problems, rushing, feeling panicked so that there are some steps that are forgotten to be made, lack of mastery of the material, lack of focus and carelessness in working on problems. Keywords– Error Analysis, Problem solving, Polya